Pengaruh Latihan Jump Rope Terhadap Power Otot Tungkai Pada Atlit Usia Dini Di Klub Vodesa Ayah Kabupaten Kebumen: Penelitian - Puput Widodo; Tahmid Akbar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The problem that arises is the unknown effect of Jump Rope Training on leg muscle strength. This study aims to determine whether or not there is an effect of jump rope training on leg muscle strength in athletes at the VODESA Ayah club which is produced in the form of pretest and posttest scores through a pre-experimental approach, namely Pre-Experimental (Pre-Experimental) for volleyball athletes at the VODESA club using the jump rope training method. This study uses a quantitative approach using a descriptive research design. The instruments in this study used survey tests and vertical jump skill measurement tests. The subjects used in this study were 20 people. The results of data analysis, testing of research results, as many as 2 people (10%) were in the very good category, 6 people (30%) were in the good category, 3 people (15%) were in the sufficient category, 9 people (45%) were in the less category, and 0 people (0%) were in the very less category. So it can be concluded that the effect of jump rope on leg muscle power in Vodesa athletes in the jump rope category is in the less category.